In vitro acaricidal assessment of betel leaves (Piper betle) aqueous and ethanol extracts on brown dog tick (Rhipicephalus sanguineus) - Shamsi, Muhammad Hafiz (2017)
The brown dog tick, Rhipicephalus sanguineus, is found worldwide with high tendency to feed on dogs and other mammals and human while spreading various types of pathogens. Various synthetic chemicals are available to treat the infestation. The main objective of this study was to find a natural alternative as a potential anti-tick compound. Naturally, betel leaves was chosen as it has many ascribed phytochemicals.The brown dog ticks were collected from stray dogs compounded at Vector Control Unit, Kuala Lumpur City Municipal, using forceps and kept alive in modified specimen containers. Fresh P. betle leaves were collected from the University’s Agriculture Park, Universiti Putra Malaysia. The leaves were dried in hot-air oven and grounded using bench-top grinder. Later the powder was soaked in ethanol and water dilutions, filtered and dried using the rotary evaporator to obtain the crude extract. Two different set of experiments were set-up, whereby ticks were exposed to both of the extracts prepared in dilutions ranging from 50 to 5−4 . Results from both experiments showed significant effect of the betel leaves as acaricide with the lethal dose from one to five dilutions of the pure extract. The ethanol extract have higher efficacy with 26 out of 50 ticks died (52%), meanwhile for the aqueousextract only 8 ticks died out of 50 (16%). In conclusion, the betel leaves ethanolic extract showed the potential to be used as acaricides for R. sanguineus.